E03 Cardio-pulmonary exercise testing aids chronic obstructive pulmonary disease diagnosis in the perioperative evaluation of patients undergoing radical cystectomy - Jarvis, Daisy; Dewar, Amy; Tetlow, Nicholas; Stephens, Robert; Meyler, Samuel (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung condition distinguished by structural changes and mucus build-up which causes dyspnoea. COPD is universally diagnosed by a spirometry test. A Forced Expiratory Volume in one second (FEV1)/Forced Vital Capacity (FVC) of <0.7, is often used to justify COPD diagnosis (Hopkinson et al., 2019, Brit Med J, 366, l4486). Reliance on spirometry tests alone may only highlight airway obstruction and not identify other consequences of COPD like impaired gas exchange which is implicated in the development of postoperative pulmonary complications. Cardio-pulmonary exercise testing (CPET) provides a more detailed look into the pathophysiology of COPD and is routinely used in perioperative settings to determine a patient’s fitness for surgery. The aims of this study were to 1) identify the number of bladder cancer patients with undiagnosed COPD, and 2) compare COPD-related CPET variables between bladder cancer patients medically diagnosed with COPD (COPDMED) who had the potential to be diagnosed at the time of CPET (COPDCPET) and those without COPD (non-COPD). All testing was performed per the American Thoracic Society/American College of Chest Physicians guidelines (2003, Am J Resp Crit Care Med, 167, 211-277). COPD-related CPET variables recorded included Minute Ventilation (V̇E; L·min-1), Peak Oxygen Consumption (V̇O2peak; mL·kg-1·min-1), the Anaerobic Threshold (AT; mL·kg-1·min-1), Ventilatory Equivalence for Carbon Dioxide (V̇E/V̇CO2), Breathing Reserve (BR; %). Eighty-two patients with bladder cancer (COPDMED [n=9], non-COPD [n=73]) underwent preoperative spirometry and CPET. In the non-COPD patients, 21 (29%) had an FEV1/FVC< 0.7, indicative of COPD and thus groups as COPDCPET. Within the COPDCPET group, 8 (40%) had an FEV1 between 50-70% of predicted which indicated moderate COPD. There was no difference found in all CPET variables measured between COPDMED and COPDCPET (P > 0.05). When COPDMED and COPDCPET were combined and compared against the non-COPD, there was a difference found in their median (95% CI) V̇Erest (13.3 [12.3-14.2] vs 11.75 [11.2-12.6] L·min-1, P = 0.02, g = 0.28). V̇O2peak (14.95 [13.64-18.12] vs 17.16 [16.35-19.11] mL·kg-1·min-1, P = 0.049, g = 0.29). V̇E/V̇CO2 at the AT (38 [36-40] vs 36 [34-37], P = 0.04, g = 0.49). There was also a difference in mean +/- SD BR (36 +/- 17 % vs 47 +/- 14 %, P = 0.004, g = 0.69). This study demonstrates the underdiagnosis of COPD in perioperative settings. Future research should assess the use of targeted COPD optimisation preoperatively.